2021
DOI: 10.1051/0004-6361/202039362
|View full text |Cite
|
Sign up to set email alerts
|

Dust observations from Parker Solar Probe: dust ejection from the inner Solar System

Abstract: Context. The FIELDS instrument onboard Parker Solar Probe (PSP) observes dust impacts on the spacecraft. The derived dust flux rates suggest that the particles originate from the vicinities of the Sun and are ejected by radiation pressure. Radiation pressure typically ejects particles of several 100 nm and smaller, which are also affected by the electromagnetic force. Aims. We aim to understand the influence of the electromagnetic force on the dust trajectories and to predict the dust fluxes along the orbit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…As further described in Pusack et al (2021), these differences are also suggestive of a Geminids β-stream. We note that grains that are smaller than the detected β-meteoroids and affected by electromagnetic forces have a much larger flux close to the orbital perihelia than at other parts of the orbit (Mann & Czechowski 2021), yet their detection is difficult with PSP /FIELDS due to the low expected impact charge generated by such small mass grains (Szalay et al 2021). Fig.…”
Section: Data-model Comparisonsmentioning
confidence: 75%
See 1 more Smart Citation
“…As further described in Pusack et al (2021), these differences are also suggestive of a Geminids β-stream. We note that grains that are smaller than the detected β-meteoroids and affected by electromagnetic forces have a much larger flux close to the orbital perihelia than at other parts of the orbit (Mann & Czechowski 2021), yet their detection is difficult with PSP /FIELDS due to the low expected impact charge generated by such small mass grains (Szalay et al 2021). Fig.…”
Section: Data-model Comparisonsmentioning
confidence: 75%
“…From the first three orbits, it was determined that the flux of β-meteoroids varies by approximately 50%, suggesting the inner solar system's collisional environment varies on timescales of 100's of days (Malaspina et al 2020c). Additionally, nanograins with radii below 100 nm were not found to appreciably contribute to the observed impact rates from these first orbits (Mann & Czechowski 2021).…”
Section: Data-model Comparisonsmentioning
confidence: 99%
“…Szalay et al (2020) showed that the observations during the second solar encounter could be explained through particles that form as collision fragments near the Sun and then are ejected by the radiation pressure force. Mann & Czechowski (2021) showed that the same fluxes could be explained with a model that combines the collisional production of dust particles and their dynamics influenced by gravity, radiation pressure, and Lorentz force; the latter was found to have only a small effect on the particles that were observed with PSP during the second orbit.…”
Section: Introductionmentioning
confidence: 87%
“…The mass distribution of fragments is of the form m −0.76 , with the largest fragment mass specified as some (collision-velocity dependent) fraction of the target mass. A brief description of the collision model is given in Mann & Czechowski (2005), while the derivation of dust fluxes is described in Mann & Czechowski (2021). They are obtained from the dust trajectories under the influence of gravity and radiation pressure (since the Lorentz force does not have a strong influence for the considered dust sizes).…”
Section: Flux Of β-Meteoroids Comparison To Predictions and Measurements From Other Spacecraftmentioning
confidence: 99%
“…The Electromagnetic Fields Investigation (FIELDS) antenna instrument package (Bale et al 2016) during the first PSP orbits measured impact events that are consistent with the trajectories of particles under the effect of gravity and radiation pressure force (Page et al 2020;Szalay et al 2020;Malaspina et al 2020). Comparison to a dust collision and dynamics model suggests that the majority of detected particles are 30 nm and larger (Mann & Czechowski 2021). The trajectory of the PSP is evolving, with the orbit perihelion approaching the Sun.…”
Section: Introductionmentioning
confidence: 94%